Traditional, Ethnomedical, and Pharmacological uses of Celastrus paniculatus: Review - Rajendra, Dr. Wudayagiri (Asian Journal of Pharmaceutics (AJP), 2019)
The medicinal plants are playing a pivotal role in the modern medicine; especially in the treatment of different human ailments. Bioactive factors derived from the plants remain the basis for a large proportion of the commercial medication. Celastrus paniculatus (CP) is one such a traditional ayurvedic medicinal plant used for centuries as a memory enhancing, anti-inflammatory, analgesic, sedative, antiepileptic, antioxidant, wound healing, anxiolytic activities, enhancement of learning and memory, hypolipidemic effects, and other pharmacological agents. The various extracts of CP have been extensively investigated in several laboratories for their neuropharmacological effects, and a number of reports are available confirming their nootropic action. The Jyothismathi oil obtained from the seeds of CP, widely used in the indigenous system of medicine for the treatment of brain-related disorders. Keeping in the view of the therapeutic potential of this plant, investigations are being continued to design novel drugs for many ailments from this versatile medicinal plant.